Intoleransi Sebagai Dampak Inkonsistensi antara Konsep dan Praktik Bermain pada Anak Usia Dini - Jumiatmoko, Jumiatmoko; Syamsudin, Amir (Jambura Early Childhood Education Journal, 2024)
Intolerance often occurs in early childhood. This is in line with a shift in playing practices. The purposes of this study were to identify the construction of the concept of play related to the development of tolerance and the implementation of play which has the potential to influence intolerance in early childhood. A literature review with stages of scoping, selecting, searching, analyzing, synthesizing, and reporting was used to examine the formulation of playing concepts from 12 relevant expert. As a result, there is a mismatch between the concept and practice of play which has the potential to develop intolerance in early childhood.